Lactic acid separation from fermented whey using electrodialysis - Machado, Ana; Gorrochotegui, Leopoldo; Cárdenas, Antonio (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this work, the acid separation from Bonsalut cheese fer mented whey, with an Asahi Glass Co electrodializer, model CH-0, was studied. Sweet whey was used and was fermented under laboratory conditions (temperature range 18-24°C). The whey was characterized by titrable acidity, pH, conductimetry, proteins by the Kjedahl method, fats by the Gerber method, lactose by picric acid fotometry and sodium and potassium by atomic absorption. The de-acidification was followed by conductimetry, pH measurements and titrable acidity. The results show that it is possible to separate 78% of the acid and 90% of the salts. They also show that the salts are separated first, be cause the ions of the salts have a higher mobility than the ions of the acid, which is mostly lactic acid. These results suggest that to separate lactic acid from fermented whey with a high concentration of salt the process should be carried out in two steps, the first to separate the salt and the second to obtain the acid.